Rickham's Neonatal Surgery (Springer London, 2018)
This book provides a detailed guide to neonatal surgery and its related disciplines including: fetal medicine, fetal surgery, radiology, newborn anaesthesia, intensive care, neonatal medicine, medical genetics, pathology, cardiac surgery, and urology. The book aims to cover all the latest advances in newborn surgery, with contributions from the basic sciences and laboratory research to reflect the steady progress in our current working knowledge and understanding of many neonatal surgical disorders. As huge advances have been made in neonatal surgery in the past decades, ethical issues, long term outcomes, and quality of life are also emphasised. This book is an authoritative reference for surgical residents in training, consultant surgeons, general surgeons with an interest in paediatric surgery, neonatologists, paediatricians, intensive care specialists, and nursing staff.